Magnetic properties of (Ga, Mn)As (110) epitaxial films. (31st May 2017) - Ma, Jialin; Wang, Hailong; Yu, Zhifeng; Wang, Xiaolei; Zhao, Jianhua
Abstract: Magnetic properties of (Ga, Mn)As films epitaxied on GaAs (110) substrates have been investigated. Both magnetic and magnetotransport measurements indicate dominant in-plane magnetic anisotropies for as-grown and annealed samples. Moreover, obvious in-plane spin reorientation transition upon the change of temperature has been observed for the as-grown samples, which disappears after annealing. The above phenomena are shown to be correlated with the competition between the cubic and the uniaxial magnetic anisotropic fields. The relative strengths of these two terms are quantitatively obtained by the planar Hall measurements and can be tuned by annealing. For all the annealed (Ga, Mn)As (110) films, a dominant [−110] uniaxial magnetic easy axis is found and the mechanism is discussed. Our work provides useful information for understanding the origin of magnetic anisotropies in (Ga, Mn)As films.